Polimerasa Chain Reaction (PCR) detection of Brucella sp. in bovine blood. (Gaceta de Ciencias Veterinarias, 2016)
The main objective of this research was to standardize specific and partial genomic sequences of Brucella genus: genes 16S rRNA, and omp from blood of seropositive cattle, in order to confirm results reached by serologic tests. A herd of 31 bovines was selected and identified as seropositive to brucelosis by official serological tests. The program Epidat 3.1 was chosen to determine sensitivity and specificity of those serological tests, against the Polymarase Chain Reaction (PCR). Bengala Rose (BR), slow seroagglutination in tube (SST), and 2 mercaptoethanol (2ME) tests were the official serological assays used. 2ME showed a sensitivity of 100%, and a specificity of 88% was found for the BR test, whereas the correlation (by Kappa Index) was discrete for the test RB when related to the PCR test. With regard to PCR amplification of selected genes was successful in a 16% (5 out of 31) of blood samples tested collected from true positives to brucelosis. In conclusión, PCR is a very important diagnostic tool to advance in the bovine brucelosis control in Venezuela, since it avoids the culling of valuable animals, and it discovers false negatives, which would stay in farms as a source of infection for other herds.
Keywords: Bovine; diagnosis; PCR; Brucella abortus; blood